Faktor-Faktor Yang Memengaruhi Share Price Sebelum Dan Setelah Periode Konvergensi IFRS - Jesslyn Faustina M, Herlin Tundjung S (Jurnal Paradigma Akuntansi, 2021)
This study aims to analyze the value relevance of accounting information consisting of earnings per share, book value of equity per share, operating cash flow per share, leverage, and dividend payout ratio that affect the share price before and after the IFRS convergence on manufacturing companies listed in the Indonesia Stock Exchange period 2005−2018. The research sample consisted of seven manufacturing companies and multiple linear regression analysis used in this study with EViews 11 version program. The test results concluded earnings per share does not have a significant effect on share price, book value of equity per share does not have a significant effect on share price, operating cash flow per share has a significant positive effect on share price with its value relevance increases after IFRS convergence period, leverage does not have a significant effect on share price, and dividend payout ratio has a significant positive effect on the share price with its value relevance decreases after the IFRS convergence period. The implication of this study is the need to increase value relevance of accounting information, namely operating cash flow per share and dividend payout ratio to help stakeholders, especially investors, in making investment decision which will provide a good signal for investors.